2010
DOI: 10.4097/kjae.2010.59.3.179
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perioperative esmolol infusion on the postoperative nausea, vomiting and pain after laparoscopic appendectomy

Abstract: BackgroundPerioperative opioid administration results in postoperative nausea and vomiting (PONV) and acute opioid tolerance that manifests in increased postoperative pain. Esmolol is an ultra short acting cardioselective β1-adrenergic receptor antagonist, and it has been successfully used for perioperative sympatholysis and it reduces the opioid requirement during total intravenous anesthesia. We tested the hypothesis that perioperative esmolol administration results in decreased PONV and postoperative pain.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 26 publications
2
35
0
3
Order By: Relevance
“…Another study that was mentioned in the meta-analysis found similar results after laparoscopic appendectomy, in that patients received less total remifentanil when they were also given an esmolol infusion, compared with patients receiving only remifentanil. 26 This latter study's opioidsparing effect was also associated with reduction of both postoperative nausea/vomiting and postoperative pain. 26 However, it should be noted that the decreased remifentanil administration in both studies may have resulted from a blunted sympathetic hemodynamic response (ie, tachycardia) after esmolol administration.…”
Section: Descriptions Of Some Clinical-antinociceptive Studies Involvmentioning
confidence: 78%
“…Another study that was mentioned in the meta-analysis found similar results after laparoscopic appendectomy, in that patients received less total remifentanil when they were also given an esmolol infusion, compared with patients receiving only remifentanil. 26 This latter study's opioidsparing effect was also associated with reduction of both postoperative nausea/vomiting and postoperative pain. 26 However, it should be noted that the decreased remifentanil administration in both studies may have resulted from a blunted sympathetic hemodynamic response (ie, tachycardia) after esmolol administration.…”
Section: Descriptions Of Some Clinical-antinociceptive Studies Involvmentioning
confidence: 78%
“…51,52 Although not frequently considered to augment pain control, esmolol infusions have also been demonstrated to decrease opioid usage in the postoperative period. 53,54 …”
Section: Steroidsmentioning
confidence: 98%
“…В анесте зиологичекой практике наибольшей популярностью, в силу короткого действия и хорошей управлемости эффектом, поль зуется эсмолол. Механизм антиэметогенных влияний эсмоло ла пока точно не определен, однако в исследованиях показано, что применение инфузии эсмолола во время анестезии вплоть до экстубации снижает частоту ПОТР [56,57]. Предположи тельно противорвотную активность препарата связывают с на личием у него антиноцицептивных свойств или способности снижать развивающуюся интраоперационно толерантность к опиоидным анальгетикам, что позволяет уменьшить дозы опи оидов как во время операции, так и в послеоперационном пе риоде.…”
Section: современное состояние проблемы профилактики потрunclassified
“…Предположи тельно противорвотную активность препарата связывают с на личием у него антиноцицептивных свойств или способности снижать развивающуюся интраоперационно толерантность к опиоидным анальгетикам, что позволяет уменьшить дозы опи оидов как во время операции, так и в послеоперационном пе риоде. [56,57]. Таким образом, представляет интерес определе ние места β 1 адреноблокаторов короткого действия в схемах профилактики ПОТР.…”
Section: современное состояние проблемы профилактики потрunclassified